Hydrogeologic and Thermal Effects of Glaciations on the Intracontinental Basins in Central and Northern Europe - Frick, Maximilian; Cacace, Mauro; Klemann, Volker; Tarasov, Lev; Scheck-Wenderoth, Magdalena (Frontiers in Water, 2022)
We use a fully coupled hydro-thermal model (TH) to quantify changes in the pore pressure and temperature distribution following the Last Glacial Maximum (LGM) in the intracontinental basins in Central and Northern Europe. We demonstrate that the system is at present-day in a state of hydrogeologic and thermal disequilibrium as a result of the past ice sheet dynamics. We find that the local geology exerts an additional control on the subsurface response to imposed glacial loading, as evidenced by a contrasting thermal and pore pressure configuration in time and space. Highest rates of pore pressure dissipation are restricted to crustal domains that underwent substantial glacial loading, while the majority of the sedimentary sub-basins show a prominent signature of hydraulic disequilibrium (overpressure) at present. Groundwater-driven convective cooling and heating during the advance and retreat of the ice cap occurred mainly within sedimentary rocks, domains where thermal equilibration is an ongoing process. The spatial correlation between modelled pore pressure dissipation rates and postglacial uplift rates is indicative of a complex and transient hydrogeological system structurally connected to the viscous tail of the ongoing isostatic adjustment after the LGM, with important implications for assessing the long-term mechanical stability of this intraplate setting.